Drivers of university–business cooperation of university faculty from the social cognitive theory perspective - Zhang, Hongwei; Chen, Xiyue; Lv, Yang; Li, Mengru (Frontiers in Psychology, 2022)
As an independent research field, there is growing attention to university–business cooperation (UBC). However, few studies focus on the driving factors of UBC, which remains an open problem in this area. This study analyzes a broad mix of drivers underlying seven UBC activities, namely, curriculum development and design (CDD), student mobility (SD), lifelong learning (LLL), professional mobility (PM), research and development (R&D), commercialization (COM), and entrepreneurship (ENT), and discusses the internal mechanism and external environment of higher education institutions (HEIs) as the moderator variable affecting UBC activities and individual motivations. Specifically, based on the social cognition theory, the independent variables include motivations (money, career, research, education, and social), the internal mechanism (support mechanism, strategic mechanism, and management mechanism), and the external environment (policy environment, economic environment, and cultural environment) are designed. The aforementioned seven UBC activities are taken as dependent variables. This work takes university faculty as the research object. Through empirical analysis, it demonstrates that the combination of driving factors of different UBC activities has its particularity. Furthermore, the results showed that the internal mechanism and external environment of HEIs could positively moderate the relationship between individual motivations and UBC activities. In terms of theoretical contribution, this study reveals the combination of factors that drive university faculty to engage in UBC. On the other hand, it can provide a reference for policymakers and managers to better development of UBC.